The Influence of Service Quality and Customer Value on Customer Trust with Customer Satisfaction as a Mediating Variable (Study at PT PLN (Persero) UP3 Banten Utara) - Lia Edli Syaravina; Alimuddin Rizal Rivai (Dinasti Publisher, 2025)
This study examines the influence of Service Quality and Customer Value on Customer Trust, mediated by Customer Satisfaction, at PT PLN (Persero) UP3 Banten Utara. The research uses a quantitative method with a survey approach involving 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression and the Sobel test. The results indicate that Service Quality and Customer Value have significant positive effects on Customer Satisfaction. Furthermore, Service Quality and Customer Satisfaction significantly affect Customer Trust, while Customer Value does not directly influence trust. Mediation analysis reveals that Customer Satisfaction significantly mediates the effect of Customer Value on trust but does not mediate the relationship between Service Quality and trust. The findings emphasize that while high perceived value builds satisfaction, consistent service quality plays a more crucial role in earning customer trust.